VANTAGE 095: An International, Multicenter, Open-Label Study of Vorinostat (MK-0683) in Combination with Bortezomib in Patients with Relapsed and Refractory Multiple Myeloma - Siegel, D.S.; Dimopoulos, M.; Jagannath, S.; Goldschmidt, H.; Durrant, S.; Kaufman, J.L.; Leleu, X.; Nagler, A.; Offner, F.; Graef, T.; Eid, J.E.; Houp, J.; et al. (Clinical Lymphoma, Myeloma and Leukemia, 2016)
Background The present global, open-label, single-arm, multicenter, phase IIb study was designed to determine the efficacy and tolerability of oral vorinostat combined with standard doses of bortezomib in patients with multiple myeloma considered refractory to novel myeloma agents. Patients and Methods Eligible patients were age ≥ 18 years, had received ≥ 2 previous regimens, had disease refractory to ≥ 1 previous bortezomib-containing regimen, and had received ≥ 1 dose of an immunomodulatory drug (thalidomide or lenalidomide)-based regimen. The patients received 21-day cycles of bortezomib (1.3 mg/m2 intravenously on days 1, 4, 8, and 11) plus oral vorinostat (400 mg/d on days 1-14). Oral dexamethasone, 20 mg, on the day of and the day after each dose of bortezomib could be added for patients with progressive disease after 2 cycles or no change after 4 cycles. The primary endpoint was the objective response rate. Results The objective response rate was 11.3% (95% confidence interval, 6.6%-17.7%), and the median duration of response was 211 days (range, 64-550 days). The median overall survival duration was 11.2 months (95% confidence interval, 8.5-14.4 months), with a 2-year survival rate of 32%. The frequently reported adverse events were thrombocytopenia (69.7%), nausea (57.0%), diarrhea (53.5%), anemia (52.1%), and fatigue (48.6%); the overall safety profile was consistent with that of bortezomib and vorinostat. Conclusion The combination of vorinostat and bortezomib is active in patients with multiple myeloma refractory to novel treatment modalities and offers a new therapeutic option for this difficult-to-treat patient population (ClinicalTrials.gov identifier, NCT00773838). © 2016 Elsevier Inc.
Keywords: Combination therapy; Efficacy; Histone deacetylase inhibitor; proteasome inhibitor; safety